P093 PLASMA PROTEINS PROFILE AND THERAPEUTIC RESPONSIVENESS IN PATIENTS WITH PREECLAMPSIA - Pinto-Souza, Caroline Cristina; Kaihara, Julyane Natisumi Saito; Mendonça, Bruna Cavecci; Mastella, Moises Henrique; Rossini, Bruno Cesar; Cavalli, Ricardo Carvalho; Santos, Lucilene Delazari dos; Sandrim, Valéria Cristina (Wolters Kluwer, 2024)
Preeclampsia (PE) is a hypertensive syndrome of pregnancy, characterized by target organ damage, related to a high incidence of cardiovascular sequelae. PE requires antihypertensive drug therapy, however, about 40% of patients do not respond to this treatment, leading to worse clinical outcomes. Through the proteomic strategy, we 1) compared the profile of circulating proteins expressed in 10 responsive (R-PE) and 10 non-responsive to antihypertensive therapy (NR-PE), besides 10 healthy pregnant (HP); 2) investigated which proteins are differentially expressed between the groups and 3) found out which signaling pathways are altered between them. The study followed the Declaration of Helsinki and was approved by the Research Ethics Committee of the Ribeirao Preto Medical School, University of Sao Paulo (FMRP-USP, protocol code CAAE-37738620.0.0000.5440). We performed plasma protein quantification using mass spectrometry, the obtained data underwent bioinformatics analyses based on Uniprot, PatternLab for Proteomics, String and MetaboAnalyst softwares. Considering a fold change of 1.5, three proteins showed as significantly differentially expressed between HP and R-PE, one downregulated (transtyretin) and two upregulated (apolipoprotein C1 and hemoglobin subunit beta). Between HP and NR-PE, there were six, two downregulated (clusterin and plasmin heavy chain A) and four upregulated (apolipoprotein A-IV; heparin cofactor II; complement C4B and haptoglobin related protein). Between R-PE and NR-PE there were four, one downregulated (fibronectin) and three upregulated (pregnancy-specific beta-1-glycoprotein 1 (PSG1); complement C4B (C4B) and complement C4A (C4A). Regarding PE, C4A and C4B intensity peaks were correlated with blood pressure and creatinine levels. Both, together with PSG1, showed significant correlations with the newborn's weight and gestational week (all p< 0.05). These findings help to understand the pathophysiological mechanisms between the two subgroups of the disease, since the under regulated circulating proteins act in the blood pressure modulation and the upregulated may occur as compensatory mechanisms due to an inflammatory scenario. These data give insights to explain the complexity and clinical consequences of this disorder.